PENGARUH DOSIS KOMPOS AZOLLA DAN PUPUK FOSFAT ALAM TERHADAP KETERSEDIAAN FOSFOR DAN HASIL KACANG TANAH PADA ALFISOLS - Mohammad Denny Permana; Sumarno Sumarno; Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : The Effect Of Azolla Compost and Phosphate Rock Fertilizer Doses on Phosphor Availability and Yield of Peanut on Alfisols. The purpose of this experiment was to determine the best doses combination of azolla compost and phosphate rock which gives the highest availability P and peanut yield. The experiment was conducted from May to November 2012 at Dryland Research Center Faculty, at Jumantono subdistrict, Karanganyar and Soil Chemistry and Fertility Laboratory of Agriculture University of Sebelas Maret Surakarta. The experiment design used was completely randomized design (CRD) with the treatments combination of azolla compost and phosphate rock fertilizers i.e P0 (without treatment), P1 (75 kg ha-1 of phosphate rock), P2 (150 kg ha-1of phosphate rock), P3 (2,5 tons ha-1 azolla compost), P4 (2.5 tons ha-1 azolla compost and 75 kg ha-1of phosphate rock ), P5 (2.5 tons ha-1 azolla compost and 150 kg ha-1 phosphate rock), P6 (5 tons ha-1 of compost azolla), P7 (5 tons ha-1 of azolla compost and 75 kg ha-1 phosphate rock), and P8 (5 tons ha-1 azolla compost and 150 kg ha-1 of phosphate rock) and P9 (5 tons ha-1 manure) and P10 (50 kg ha-1 of urea, 100 kg ha-1 SP36, and 75 kg ha-1 KCl) as comparison treatments. The planting was conducted in the 30x40 cm pots filled with 12 kg of finely soil passes 2mm filter. Each pot planted with 3 seeds peanuts, then reduced to one crop per pot at 14 days after planting. Data were analyzed by F test 95% confidence level, if there is a significant influence followed by DMRT at 95% confidence level. Variables for this experiment are phosphor avaibility, CEC, organic matter, total N in the soil, fresh biomass and dry biomass peanut,height of the plant, fresh weight of pods, dry weight of pods, number of pods, dry seed weight and number of seed. The results showed that the best dose treatment was P8 which gives the highest of availability phosphor (13,01 ppm) and peanut yield (1,96 tons ha-1)